Strategi Penuntutan Kejahatan Siber dengan Artificial Intelligence di Era Digital - Tania, Cindy; Gidalty, Janwan (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The rapid escalation of cybercrime in Indonesia and worldwide highlights the urgent need for adaptive legal strategies that integrate emerging technologies. This study investigates how Artificial Intelligence (AI) can be used to strengthen prosecution strategies against cybercrime, focusing on law enforcement readiness, implementation challenges, and the opportunities it presents. Using a qualitative approach supported by empirical data, the research combines doctrinal legal analysis, socio-legal perspectives, and case studies through in-depth interviews with prosecutors, investigators, and digital forensic experts, alongside secondary data from national and international reports. The results reveal that while awareness of AI’s potential is relatively high, its actual use in legal practice remains limited, with only 30 percent of respondents having direct experience with AI tools. Statistical data also confirm a significant increase in cyberattacks from 215 million anomalies in 2022 to nearly 400 million in 2024, underscoring the urgency of adopting AI. Findings show that AI can enhance the identification of digital evidence, detect hidden patterns in cyberattacks, and improve the effectiveness of prosecution. However, concerns about algorithmic bias and the lack of legal frameworks persist. This study contributes to academic discourse by offering an applied framework for AI-based prosecution strategies in developing countries and by providing practical recommendations for prosecutors and policymakers to accelerate digital legal reforms. The novelty lies in bridging theoretical discussions with an operational model contextualized to Indonesia’s legal environment.